COMPARISON OF DIFFERENT VERSIONS OF THE Midjourney AND ITS USE IN VARIOS SPHERES OF CREATION VISUAL CONTENT - PETRYNA, DMYTRO; KORNUTA, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
To date, the use of applications for the generation of illustrative material with the help of artificial intelligence (AI) is one of the most progressive for creating content in the field of visual occupations (designers, architects, artists), for marketers, students and ordinary people. The main reason for using neural networks is to save time and create inspiring examples in any field of human activity. Currently, there are more than 20 independent programs that generate visual content, and many companies such as Adobe and Canva use neural network tools. The use of artificial intelligence is irreversible and requires practice and some experience in its work with the creation of visual content. The development and updating of the main programs in this direction, such as Midjourney and Leonardo, is constant and needs to be studied. The photo-realism and image detailing of the latest versions of Midjourney allows you to create visual content that can be used to generate new ideas and use it for creation quality visual content for advertising. The article compares the quality parameters of the visual content created on the basis of artificial intelligence by the Midjourney program using its different versions. The updates from the initial version to the latest V6.0 were phased in less than a year and a half. Certain deviations in the images are considered, which leads to the impossibility of their further use. Analyzed the parameters of writing explanations (promts), which will affect the final quality of the generated image, the possibility of writing complex promts with one and several images, as well as advanced promts. The possible use of neural networks that work with text for targeted writing of appropriate prompts for better automation of the generation process is considered. The article considers the possible use of the Midjourney program for various spheres of human activity that use various images, and also raises the question of the role of a person as the main creator and generator of creative ideas.